Estimation of Fisetin in Strawberry (Fragaria ananassa) by UV-Vis Spectrophotometry - Subhadip Chakraborty; Nalanda Baby Revu; Gita Surisetty (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2024)
Flavonoids are naturally occurring plant molecules. Fisetin belongs to a class of flavonoids; it is a bioactive polyphenolic flavanol molecule found in fruits and vegetables with potential pharmacological activities. This study was designed to validate a simple method for estimating and evaluating fisetin in the strawberry extract by spectrophotometry. Methodology: Isolation of fisetin from the methanolic extract of Fragaria ananassa with chloroform by liquid-liquid extraction technique. The wet granulation method was formulated for making the tablet by incorporating pure fisetin as a biomarker. Spectrophotometric detection was carried out at an absorption maximum of 362 nm using methanol as solvent. The method was validated by linearity, accuracy, and precision studies. In the validation study, fisetin obeyed Beer-Lambert's law in the concentration range of 1 to 8 µg/mL, and it was found to be linear with a correlation coefficient of 0.99, and the regression equation was found to be Y= 0.10x -0.04. Found the percentage relative standard deviation among all the responses was less than 2%, indicating the method's precision. The percentage recovery of fisetin was found to be in the range of 96.61 to 101.63%. The present study was statistically confirmed. Therefore, the proposed approach can accurately measure the active marker compound in the crude drug (fisetin). The analysis allows the optimization of a precise method for determining the fisetin in the fruit of Fragaria ananassa, which can be used to support the quality assessment of this herbal material.